Biopsychosocial Aspect of Pregnant Women Suspected Brainstem Death: Aspek Biopsikososial pada Perempuan Hamil dengan Kecurigaan Mati Batang Otak - Dwiana Ocviyanti; Ribkhi A. Putri (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objectives: Diagnosis of brainstem death and the vital organ function support in the pregnant woman to prolong gestation to attain fetal viability is still controversial. The decision is influenced by ethical and legal issue in the country. Another consideration is the hospital cost and health insurance coverage. This article purpose is to report a case and discuss the biopsychosocial aspect of this issue, so the doctors know how to decide a similar case.Methods: We reported a suspected brainstem death in pregnant women and discussed the holistic approach.Case: This case is a-38-year-old women, third pregnancy, 22 weeks of gestation, referred from the secondary hospital in a comatose condition. She was diagnosed with brainstem dysfunction due to intracranial mass and cerebral oedema. She wasn't diagnosed with brainstem death due to the electrolyte imbalance that can cause this condition. We did the multidisciplinary management approach. We decided the termination of pregnancy would only be performed if the fetus reaches 28 weeks of gestational age (with survival rate on perinatology is 31%). From the husband point of view, since the attending doctors have not declared the mother to be dead, then the husband still want to keep the mother in full life support. The patient and the fetus died on the 8th day of hospitalization. The patient was fully paid for by Indonesian Health Insurance.Conclusion: Maternal brainstem dysfunction and brainstem death during pregnancy are rare. In Indonesia, ethical and legal consideration to keep both mother and fetus are appropriate with the general social, cultural, and religious values. However, we recommend managing every single case individually with an intensive multidisciplinary approach due to the possibility of the different personal value of the patient.Keywords: brainstem dysfunction, brain death, pregnancy, fetal, ethic, legal. Abstrak Tujuan: Diagnosis kematian batang otak dan dukungan fungsi organ vital pada perempuan hamil untuk melanjutkan kehamilannya sampai janin dapat hidup jika dilahirkan masih kontrovesi. Keputusan ini dipengaruhi oleh etik dan hukum di suatu negara. Pertimbangan lainnya adalah biaya perawatan rumah sakit dan cakupan asuransi kesehatan. Artikel ini bertujuan melaporkan sebuah kasus dan mendiskusikan aspek biopsikososialnya, sehingga para dokter dapat mengambil keputusan pada kasus lain yang serupa.Metode: Kami melaporkan kasus perempuan hamil dengan kecurgaan kematian batang otak dan mendiskusikan pendekatan holistiknya.Hasil: Kasus perempuan usia 38 tahun, kehamilan ketiga, 22 minggu, dirujuk dari rumah sakit sekunder dalam kondisi koma. Pasien didiagnosis dengan disfungsi batang otak akibat massa intracranial dan edema serebri. Pasien tidak didiagnosis dengan meti batang otak karena kondisi ini masih dapat dikarenakan gangguan keseimbangan elektrolit. Kami melakukan pendekatan multidisiplin. Diputuskan terminasi kehamilan akan dilakukan hanya jika janin mencapai usia kehamilan 28 minggu (dengan harapan hidup dari perinatology 31%). Dikarenakan dokter belum mengatakan pasien sudah meninggal, suami pasien menginginkan pasien dalam topangan alat. Pasien dan janinnya meninggal pada hari ke-8 perawatan. Pembiayaan pasien dengan menggunakan BPJS.Kesimpulan: Disfungsi batang otak dan kematian batang otak selama kehamilan adalah kasus yang jarang. Di Indonesia, etik dan hukum yang berlaku untuk menjaga kehidupan ibu dan janin sesuai dengan nilai sosial, budaya, dan agama. Namun demikian, kami merekomendasikan mlakukan tata laksana setiap kasus secara individu dengan pendekatan multidisiplin dikarenakan perbedaan nilai pribadi pasien dan keluarga.Kata kunci: disfungsi batang otak, etik, hukum, janin, mati batang otak, kehamilan.